2022
DOI: 10.3389/fpsyt.2022.925476
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging of the dopamine system in schizophrenia – A scoping review

Abstract: For decades, aberrant dopamine transmission has been proposed to play a central role in schizophrenia pathophysiology. These theories are supported by human in vivo molecular imaging studies of dopamine transmission, particularly positron emission tomography. However, there are several downsides to such approaches, for example limited spatial resolution or restriction of the measurement to synaptic processes of dopaminergic neurons. To overcome these limitations and to measure complementary aspects of dopamine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 173 publications
1
0
0
Order By: Relevance
“…Our previous studies in mice with a homozygotic deletion of Glud1 in CNS (C-Glud1 -/mice) revealed elevated hippocampal cerebral blood volume (CBV) and glutamate levels in medial PFC (mPFC) and hippocampus, along with baseline and amphetamine-induced hyperlocomotion. These ndings resonate with human schizophrenia data showing decreased Glud1 expression 14 , elevated hippocampal CBV and glutamate/glutamine (Glx) levels 17,18 and a hyperdopaminergic response to amphetamine 19 . C-Glud1 -/mice also show prominent abnormalities in tasks relevant to cognitive impairment in schizophrenia, including working, spatial and social memory tasks and reversal and extra-dimensional set shifting (EDSS) in the Water T-maze 14,20 .…”
Section: Introductionsupporting
confidence: 83%
“…Our previous studies in mice with a homozygotic deletion of Glud1 in CNS (C-Glud1 -/mice) revealed elevated hippocampal cerebral blood volume (CBV) and glutamate levels in medial PFC (mPFC) and hippocampus, along with baseline and amphetamine-induced hyperlocomotion. These ndings resonate with human schizophrenia data showing decreased Glud1 expression 14 , elevated hippocampal CBV and glutamate/glutamine (Glx) levels 17,18 and a hyperdopaminergic response to amphetamine 19 . C-Glud1 -/mice also show prominent abnormalities in tasks relevant to cognitive impairment in schizophrenia, including working, spatial and social memory tasks and reversal and extra-dimensional set shifting (EDSS) in the Water T-maze 14,20 .…”
Section: Introductionsupporting
confidence: 83%
“…Currently, there is a general recognition that catecholaminergic systems play a role in schizophrenia symptomatology (Howes et al, 2023;Os & Kapur, 2009;Abi-Dargham et al, 2000;Perez-Costas et al, 2010;Tost et al, 2010;Chen et al, 2021). This view is supported by post-mortem studies on brainstem nuclei, structural studies using magnetic resonance imaging (MRI), and pharmacological studies (Rice et al, 2016;Howes et al, 2023;Schulz et al, 2022;Weinstein et al, 2017;van Kammen & Kelley, 1991). However, few studies aimed to directly measure activity in catecholaminergic structures in patients in vivo.…”
Section: Introductionmentioning
confidence: 99%